Law, Legitimacy and the Rationing of Health Care : a Contextual and Comparative Perspective. - Syrett, Keith (Cambridge law, medicine, and ethics., 2007)
Dr Syrett evaluates how courts may contribute to the attainment of legitimacy in healthcare rationing.